Sobat Gizi: Strengthening Mothers Knowledge to Prevent Underweightin Children through Nutrition Education - Syamsir; Julia Arlianti Devani; Nahara Isnaini Tri Uljanah; Alyssa Putri Anwar; Anisa Dian Agmelia Putri; Theresa Rebecca Papu (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The problem of underweight in toddlers remains a serious challenge because it impacts the growth, development, and endurance of children. Underweight can be defined as a body weight that is low due to malnutrition (Nisa, 2024). Based on WHO data (2022), there are 45 million children (6.8%) in the world experiencing underweight, while in Indonesia the prevalence reaches 17.1% (SSGI, 2022; Mulyani, 2024). In Bangun Rejo Village, Kutai Kartanegara, 13 toddlers were recorded below the KMS red line. The lack of parental knowledge about nutrition is the main cause, so the Sobat Gizi 1 and Sobat Gizi 2 programs were developed as an educational effort to increase understanding of balanced nutrition to reduce malnutrition rates in toddlers. Objective : The SOBAT GIZI program aims to enhance the knowledge, understanding, and skills of parents especially mothers with toddlers in applying proper parenting and feeding practices as a preventive and corrective measure against child malnutrition. Additionally, this program seeks to improve the nutritional status of toddlers by optimizing nutrition improvement efforts particularly in addressing the high prevalence of underweight cases in Dusun Bangun Rejo I, Bangun Rejo Village. Research Methods/ Implementation Methods : This program employed a participatory educational approach that combined nutrition counseling, interactive discussions, and hands-on activities to enhance mothers’ knowledge, attitudes, and skills in child feeding and nutrition. The implementation was carried out through collaboration among professional nutritionists, local health cadres, and village officials. Activities were conducted through a series of structured sessions under the Sobat Gizi component which focused on improving mothers’ understanding of parenting practices, balanced nutrition, and appropriate feeding behaviors through lectures, group discussions, and pre- and posttest assessments to evaluate knowledge improvement. Results : The Sobat Gizi 1 and 2 programs significantly improved mothers’ knowledge on child nutrition and parenting. In Sobat Gizi 1, scores rose from 75.5 to 95.5 (↑26.49%), with a Wilcoxon test result of Z = -3.573; p = 0.000. Likewise, Sobat Gizi 2, integrated with the Ceria Masak session, showed a significant increase (Z = -3.079; p = 0.002), with 13 participants improving and 2 remaining unchanged. Overall, both programs effectively enhanced knowledge by 26–27%, proving that interactive education and practical sessions strengthen nutritional awareness and promote positive behavioral change among mothers at Posyandu Menuju Sehat, Bangun Rejo Village